Misdiagnosis of HIV With Toxoplasmosis Encephalopathy With Progressive Memory Loss as the Initial Symptom: A Case Report - Wu, Jingjing; Luo, Xiumei; Huang, Nanqu; Li, Yuanyuan; Luo, Yong (Frontiers in Neurology, 2022)
Toxoplasmosis encephalopathy (TE) is a kind of encephalopathy parasitic disease caused by Toxoplasma gondii. It is the most common opportunistic for central system infection in patients with acquired immunodeficiency syndrome (AIDS) or human immunodeficiency virus. Without early diagnosis and proper treatment, this opportunistic infection can be life-threatening. The common clinical manifestations of the disease include altered mental state, epilepsy, cranial nerve damage, paresthesia, cerebellar signs, meningitis, motor disorders and neuropsychiatry. The most common presentation in about 75% of cases is a subacute episode of focal neurological abnormalities such as hemiplegia, personality changes, or aphasia. Imaging needs to be differentiated from multiple sclerosis, lymphoma, and metastases. We report a case of acquired immune deficiency syndrome complicated with toxoplasma encephalopathy with rapid progressive memory loss as the initial symptom and misdiagnosed as multiple sclerosis. Through the comprehensive analysis of the clinical symptoms and imaging examination of this disease, we hope to enhance the confidence of clinicians in the diagnosis of this disease.